Net climate impacts of sustainable intensification measures in boreal Finnish crop-livestock system - Rimhanen, Karoliina; Hietala, Sanna; Joensuu, Katri; Sairanen, Auvo; Virkajärvi, Perttu; Palosuo, Taru (Elsevier, 2026)
Sustainable intensification (SI) aims to increase productivity while minimizing environmental impacts and preventing land expansion. Although SI strategies are widely promoted, their overall climate mitigation potential in boreal crop–livestock systems remains uncertain. This study quantified the impacts of potential SI options on greenhouse gas (GHG) emissions and soil organic carbon (SOC) stocks in a representative Finnish dairy system. Two SI options were evaluated: (1) increasing crop yields and (2) reducing the grain proportion in dairy cow diets. Soil carbon inputs were derived from agricultural statistics and literature data, SOC stock changes were estimated using the Yasso07 soil model, and total GHG emissions were calculated with the Carbon Calculator life cycle assessment (LCA) model over 20- and 100-year horizons. Livestock processes accounted for the largest share of GHG emissions, while SOC-related emissions were mainly driven by organic soil cultivation. SI options that reduced land use for feed production, particularly on organic soils, achieved up to 38% lower total climate impact compared with the baseline. Including SOC stock changes increased total LCA-based emissions by up to 30%, emphasizing the importance of soil processes in mitigation assessments. The findings demonstrate that targeted SI strategies integrating productivity-enhancing and emission-reducing measures can effectively improve the climate performance of boreal dairy systems, supporting the transition toward carbon-neutral and climate-smart agriculture.
Keywords: sustainable intensification; crop-livestock systems; soil organic carbon; greenhouse gas emissions; life cycle assessment; boreal agroecosystems; climate-smart agriculture